Ahmed Hassan Zewail. 26 February 1946—2 August 2016. (6th June 2020) - Thomas, John Meurig
Abstract : Ahmed Zewail will forever be remembered for three main reasons: first, he was the individual who first demonstrated that the structure and dynamics of atoms in the transition state of chemical reactions could be determined through the judicious use of ultrafast lasers, in a field that he pioneered, for which he coined, called femtochemistry; second, he transformed both gas phase electron diffraction and transmission electron microscopy by improving their temporal resolution some 10 orders of magnitude, while simultaneously retaining the spatial resolution of electron microscopy at the atomic level; and third, he was the first US Science Envoy to the Middle East (appointed by President Obama). To all who knew him, he was a warm-hearted, life-enhancing person endowed with exceptional technical virtuosity as an experimentalist and a profound thinker, whose prodigality of output was also exceptional. He exhibited remarkable skills as an enterprising fundraiser in his determination to establish the Zewail City of Science and Technology on the outskirts of his beloved Cairo. He also influenced greatly the L'Oréal–UNESCO scheme for awarding prizes to women in science.